Taxonomic revision of Algero-Tunisian Pleurodeles (Caudata: Salamandridae) using molecular and morphological data. Revalidation of the taxon Pleurodeles nebulosus (Guichenot, 1850) - Carranza, Salvador; Wade, Edward (Zootaxa, 2004)
The taxonomic status of Algero-Tunisian Pleurodeles was reanalysed in the light of new molecular and morphological evidence. Mitochondrial DNA sequences (396 bp of the cytochrome b and 369 of the 12S rRNA) and the results of the morphometric analysis, indicate that Algero-Tunisian P. poireti consists of two genetically and morphologically distinct forms. One restricted to the Edough Peninsula, and another one covering all the rest of its distribution in Algeria and Tunisia. The name P. poireti (Gervais, 1835) is restricted to the population of the Edough Peninsula, while P. nebulous (Guichenot, 1850) correctly applies to all other populations in the distribution. P. poireti originated approximately 4.2 Myr ago, probably as a result of the Edough Peninsula being a Pliocene fossil island, allowing both forms of Algero-Tunisian Pleurodeles to diverge both genetically and morphologically.